Investigation on the effect of sintering temperature and composition of titanium (Ti) on electrical conductivity of al2o3/zro2/ti ceramic composites - Nur Amalina, Sabuan (2021)
Ceramic has remained one of the significant materials owing to its resistance to elevated temperature and hardness. Nevertheless, ceramics exhibit low electrical conductivity, and it is very brittle. These properties influenced the broad utilization of it in various functions. Most ceramics usually have combination of both covalent and ionic bond. The number of electrons shared indicates the force of attractions related to strength of covalent bond. In contrast, neither ionic nor covalent bonding forms free electrons like in metallic bonding. Thus, ceramic material has low electrical and thermal conductivity. For instance, the properties of low conductivity of ceramics creates difficulty in terms of machining to the obligatory form and complexity utilizing the non-conventional electrical discharge machining (EDM). The property of electrical conductivity in the ceramics can be enhanced by the accumulation of conductive metallic particles so that its microstructural property would be altered. Consequently, the electrical conductivity of ceramic matrix composite of alumina reinforced with titanium (Al2O3/Ti) with different weight (w) percentage (%) is manufactured. Pressureless sintering was utilized with temperature of 1600°C,1650°C and 1700°C to investigate for potential progress in electrical conductivity. A new-found notion on the microstructural-process interaction for the better electrical conductivity was recognized. The Al2O3/Ti ceramics was noticed in enhancing its electrical conductivity as the weight percentage (wt%) of Ti increases. Based on the Scanning Electron Microscopy (SEM) and observation of EDX, rise in the electrical conductivity is primarily attributed to the formation of interconnected Ti phases inside the alumina matrix after sintering. The formation of TiO2 after sintering additionally promotes the progress in electrical conductivity. With the constant increased of Ti content, TiO2 reacted entirely and the volumes of Ti residual also increased. The new phases are likely to be a contributing factor for the enhanced conductivity of the alumina matrix. The electrical conductivity sintered at 1600°C with 20 wt% Ti display greatest improvement in electrical conductivity of 78.795 x 10 3 S/cm related to pure of Al2O3.